Pengaruh Sumber Daya Pekerjaan, Sumber Daya Individu Dan Beban Kerja Terhadap Keterikatan Kerja Dan Dampaknya Pada Kinerja Pegawai Sekretariat Daerah Kabupaten Seluma - Nurul Iksan; Slamet Widodo; Praningrum Praningrum (UNIB Press, 2020)
The purpose of this research is to know the influence of job resources, personal resources and job demands against the work engagement officer of Seluma District secretariat. In addition, the purpose of this research is to know the role of work engagement mediation on the influence of job resources, personal resources and job demands towards the performance of district secretariat of Seluma Regency This research is a type of descriptive research with a quantitative approach. The type of data used is the primary data obtained through a questionnaire propagation. The respondents of this research were 151 officials of the Seluma District Secretariat. Data Analysis methods used descriptive analysis and SEM analysis. Based on field research, the results of which: (1) job resources variables have significant effect on employee work engagement; (2) personal resources variables have significant effect on the employee's work engagement ; (3) job Demand variables have significant effect on employee work engagement ; (4) The work engagement variables have significant effect on employee performance; (5) Work engagement has fully mediating on the influence of job resources on the employee performance of the regional secretariat of Seluma District; ( 6) Work engagement has fully mediating to the effect of personal resources on the employee's performance of the regional secretariat of Seluma District; and (7) Work engagement has fully mediating to the influence of job demand on the employee performance of the regional secretariat of Seluma District.